Changing the game : from cybersecurity to cyber resilience management : a framework designed to assist FMCG companies in shaping a cyber resilience strategy - De Jong, Madeleine (My University, 2019)
Today’s fast-evolving threat landscape makes it impossible for organizations to protect from every unique threat, and that makes it just a matter of time before a sophisticated attack occurs. Therefore, a reconsideration of the current reactive management trend of protecting technology against identified threats is desired. Cyber resilience is a business-driven security strategy that focuses on protecting the continuous business delivery - this means that not only technology, but all aspects that contribute to an organisation should be proactively protected. This thinking moves the center of gravity from trying to prevent from all risks in the pre-event phase (identifying and protecting) to-wards an organization that is safe to fail in security in a controlled way in the post-event phase (detecting, responding, recovering and adapting) to minimize the business impact. This research seeks to provide a framework that helps IT Management to move from cyber security towards cyber resilience management. This is done by combining relevant cyber resilience theories that led to a cyber resilience management framework, consisting of the phases: identify, protect, detect, respond, re-cover and adapt. By considering both academic and business literature, this research provides determinants that could be used in organizational context.
Keywords: cyber resilience, cybersecurity, information security, FMCG industry